Pro Scalable .NET 2.0 Application Designs - Rossberg, Joachim (Apress, 2012)
The idea for this book came up in 2002. We first thought about writing this as an internal document at Cap Gemini Ernst & Young. When doing research on the market, we discovered that very few books focused on the IT architect and system designer. Most books were directed toward the developer, and we wanted a book for a broader audience. Because we think many IT architects lack a thorough understanding of what they can actually achieve on aMicrosoft platform, we decided that we should extend the intended audience of our document outside Cap Gemini Ernst & Young and try publishing it as a book. Apress has always published great books, so we turned to them first. Gary Cornell became interested, and this book is the result.